2020
DOI: 10.1364/oe.409228
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of point-by-point off-axis Bragg gratings inscribed by a femtosecond laser in few-mode fibers

Abstract: Off-axis Bragg gratings with varied horizontal and vertical distances off the center in a step-index two-mode fiber were fabricated by 800 nm infrared-femtosecond laser pulses through a point-by-point technique. In this article, we experimentally investigate these gratings via measuring the transmitted power and the reflected intensity profiles under different input polarization, with multiple characteristics reported for the first time to the best of our knowledge. To highlight, we find that the birefringence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…It is attributable to the refractive index modification (RIM) induced under each grating point. This RIM is a consequence of aberrations introduced by the focusing system of the femtosecond laser during the FBG fabrication process 35,24,36 . The vertical displacement of the FBG brings the RIM closer to the central region of the fiber core.…”
Section: Diffraction Profile Of On-axis and Off-axis Fbgmentioning
confidence: 99%
See 1 more Smart Citation
“…It is attributable to the refractive index modification (RIM) induced under each grating point. This RIM is a consequence of aberrations introduced by the focusing system of the femtosecond laser during the FBG fabrication process 35,24,36 . The vertical displacement of the FBG brings the RIM closer to the central region of the fiber core.…”
Section: Diffraction Profile Of On-axis and Off-axis Fbgmentioning
confidence: 99%
“…The study discusses the influence of the grating microstructure on the observed diffraction patterns. Later, researchers analyzed side diffraction patterns experimentally [21][22][23][24] and theoretically using Volume Current Method [25][26][27][28] , Coupled Mode Analysis, 29 Free Space Model, 30,31 and Antenna Theory 31 .…”
Section: Introductionmentioning
confidence: 99%
“…32 In all reported cases, the maxima in ϕ formed perpendicular to the direction of the writing laser that imprinted the structure in the fiber. It was attributed to an irregular refractive index modification of the fiber core cross section; 19,31,33 Qui et al 34 even used this effect to find out the transverse orientation of the grating.…”
Section: ■ Introductionmentioning
confidence: 99%